Identification of novel avirulence effectors in the Dothideomycete plant pathogens, Venturia inaequalis and Cladosporium fulvum : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) in Plant Sciences at Massey University, Manawatū, New Zealand - de la Rosa, Silvia (Massey University, 2022)
Venturia inaequalis and Cladosporium fulvum are important fungal pathogens of crop species, causing scab and leaf mould disease of apple and tomato, respectively. Resistance to these pathogens is governed by Rvi (apple) and Cf (tomato) resistance (R) genes. These R genes encode immune receptors that recognize specific pathogen virulence factors, termed avirulence (Avr) effectors, to activate plant defenses. Notably, isolates or strains of V. inaequalis and C. fulvum have emerged that can overcome resistance mediated by specific R genes in their respective hosts. To better understand how these pathogens cause disease or overcome resistance, and to monitor the occurrence of resistance-breaking isolates or strains in the field, Avr effectors from V. inaequalis and C. fulvum must be identified and functionally characterized. Using a combined comparative genomics and phenotyping approach based on progeny from a sexual cross between V. inaequalis isolates that differ in their ability to overcome Rvi4 resistance in apple, a strong candidate for the corresponding AvrRvi4 effector gene was identified (Chapter 2). Similarly, using a comparative genomics approach based on in planta-expressed effector candidates from C. fulvum strains that differ in their ability to overcome Cf-9B resistance in tomato, combined with functional assays, the corresponding Avr9B effector gene was identified (Chapter 4). In the resistance-breaking isolates or strains studied, the candidate AvrRvi4 gene was disrupted, while the Avr9B gene had been deleted. Consistent with most fungal Avr effectors and their genes, both the AvrRvi4 candidate and Avr9B are highly expressed in planta, and encode small, secreted cysteine-rich proteins. The AvrRvi4 candidate forms part of an expanded protein family in V. inaequalis, with members predicted to adopt a β sandwich fold similar to structurally characterized fungal effectors. Avr9B, however, is predicted to adopt a novel protein fold. Finally, using a heterologous expression approach, three in planta-expressed candidate effectors from V. inaequalis were found to trigger defense responses in non-host plants (Nicotiana spp.), suggesting they are recognized by R proteins in these species (Chapter 3). Taken together, this thesis has increased our understanding of the molecular mechanisms responsible for the activation and circumvention of resistance by V. inaequalis and C. fulvum, which will in turn direct host cultivar deployment and disease control strategies in the field.
The following figures were removed for copyright reasons: Figure 1.2 (Jones & Dangl 2006, Fig 1); Figure 1.3 (Cook 2015, Fig 2); Figure 1.4 (He et al. 2018, Fig 1) Figure 1.15 (Gessler et al. 2006, Fig 1) Figure 1.16 (Kucheryava et al. 2008, Fig 2)
Keywords: Venturia inaequalis; Cladosporium fulvum; Plant-pathogen relationships; Genetic aspects; 310805 Plant pathology